The Power of Fertility and Its Importance for the Concept of Sustainable Development - Jakubowska, Zuzanna; Koza, Karolina; Leder, Wojciech; Owczarczyk, Aleksandra; Skorupka, Zuzanna; Wróblewski, Tomasz (Studia Ecologiae et Bioethicae, 2021)
Demographic changes are one of the indicators of sustainable development, expressed by the value of the natural increase in the human population, resulting directly from the fertility level, which is the subject of this article. Human fertility is a complex potential conditioned by the environmental, social, and economic factors. The multi-dimensional relations of fertility that may affect its level, constitute an unlimited field of research, study, and analysis. The inter-disciplinary scope of fertility research conducted by the authors has shown that fertility is an issue that, in its historical, social, political, and medical aspects, has the potential of contributing to societal development and raising the standard of living. The aim of this article is to answer the question: whether and how the fertility of an individual has an impact on the idea of sustainable development. To achieve this, the available literature was analysed and synthesised, as well as supplemented with information provided by experts in the field. The article incorporates presentations of selected fertility determining factors, methods of measuring fertility potential, and diverse contexts, such as the impact of fertility on history and its relationship with the freedom of the human individual. Moreover, the authors present the relationship between the fertility of an individual, and the assumptions and postulates of the idea of sustainable development.